Introducing the general management of glomerular disease from a pediatric perspective based on the updated KDIGO guidelines - Seon Hee Lim (Korean Society of Pediatric Nephrology, 2023)
In 2021, a new chapter on the general management of glomerulonephritis (GN) was added to the Kidney Disease: Improving Global Outcomes (KDIGO). It emphasizes the importance of early general management of GN for improving long-term kidney outcomes and prognosis. The chapter introduces the management of glomerular diseases in 18 subchapters. Here, kidney biopsy for the diagnosis and evaluation of kidney function and the management of complications, such as hypertension, infection, and thrombosis, are presented. Moreover, the adverse effects of glucocorticoids and immunosuppressive therapy, which are commonly used drugs for glomerular disease, are mentioned, and a guideline for drug selection is presented. Each subtheme focused on items reflecting the interpretation of the "practice points" of the expert working group are introduced. In this review of the general treatment for GN in the KDIGO guidelines, excluding pregnancy and reproductive health, we focused on and compared various references pertaining to pediatric GN management.